Auto Segmentation of Breast Tumor in B-Mode Ultrasound Analysis (GUB Journal of Science and Engineering, 2018)
Segmentation or lesion boundary detection in classification of Benign and Malignant breast tumors from B-Mode ultrasound image analysis is a challenging one. In this study, first a suitable frame is chosen by strain and velocity imaging from a raw radio frequency (RF) echo of clinical cases. The consequent B-Mode ultrasound (US) image is calculated and binarized. Finally, the lesion boundary is well-defined by binary dilation technique using MATLAB.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 5(1), Dec 2018 P 75-78